A NOVEL RP-HPLC METHOD FOR THE QUANTIFICATION OF RIVAROXABAN IN FORMULATIONS - DR. NALLAGATLA. VIJAYA BHASKAR RAO; BRC SEKHAR REDDY (International Journal of Pharma and Bio Sciences, 2013)
A simple, precise and accurate RP-HPLC method was developed and validated for assay of Rivaroxaban in tablet dosage form. Isocratic elution at a flow rate of 1ml/min was employed on a Kromasil C18 (250x4.6mm, 5µm in particle size) at ambient temperature. The mobile phase consisted of Methanol: Acetonitrile 80: 20 v/v, (PH 4.4). The UV detection wavelength was 273 nm and 20µl sample was injected. The retention time for Rivaroxaban was 5.35 min. The percentage RSD for precision and accuracy of the developed method was found to be less than 2%. The newly developed method was validated as per the ICH guidelines. The method was successfully applied for regular analysis of Rivaroxabanin in different formulations and bulk drug.